INTERPRETASI ZELLIGE BAHIA PALACE MELALUI TEKNIK ANYAMAN PADA BUSANA AVANT-GARDE - Laura Intan Prasyono; Urip Wahyuningsih (Universitas Negeri Surabaya, 2026)
The objectives of this study are to (1) describe the process of applying weaving techniques inspired by Zellige Bahia Palace to avant-garde fashion, and (2) determine the results of weaving techniques inspired by Zellige Bahia Palace in avant-garde fashion. Zellige Bahia Palace was chosen as the source of inspiration because it has geometric shapes and repetitive patterns typical of Morocco that are relevant to explore through weaving techniques. The type of research used is quantitative descriptive with Double Diamond method, which consists of four stages: Discover, which collects information about Zellige Bahia Palace and weaving techniques; Define, which formulates exploration in a moodboard; Develop, which designs five concept and then selects one design, explores materials, and creates prototype; Deliver, which assesses the results of avant-garde clothing by three fashion experts through an observation sheet. The results show the application of Zellige Bahia Palace elements in avant-garde fashion design is considered excellent, as demonstrated by the accuracy of translating geometric motifs into woven structures. The quality of the weaving technique received an excellent rating for its neatness, precision, and proportionality. However, the finished garments still need further development so that their experimental and innovative avant-garde character can be displayed more strongly.